2022
DOI: 10.1002/app.52492
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behavior of poly(propylene) reinforced with graphene nanoplatelets for injection molding

Abstract: Poly(propylene) (PP)‐based graphene nanoplatelets (GnPs) nanocomposites are processed by a melt blending technique. To obtain more knowledge about the rheological behavior of nanocomposites for injection molding, the rheological characterization of nanocomposites is performed using a double capillary rheometer over a shear rate range from 10 to 6000 s−1. The influence of processing temperature (170, 180, and 190°C) is evaluated. To improve the interaction between PP and GnPs, maleic anhydride (MA) is applied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…The smooth surface and no obvious phase separation between the components of B20/RES/PBS/GRA1% indicate the formation of a more homogeneous phase than B20/RES/PBS/GRA0.5%, as represented in Figure 6E,F, respectively. According to the GnPs supplier, the nanoplatelets have on their edges functional groups such as ethers, carboxyls, or hydroxyls that can facilitate the GRA distribution into the matrix [42]. The results of this study suggest that the use of RES and 1% GRA is a promising approach for developing high-performance biodegradable blends with good structural integrity for use in automotive parts.…”
Section: Morphological Analysismentioning
confidence: 89%
See 1 more Smart Citation
“…The smooth surface and no obvious phase separation between the components of B20/RES/PBS/GRA1% indicate the formation of a more homogeneous phase than B20/RES/PBS/GRA0.5%, as represented in Figure 6E,F, respectively. According to the GnPs supplier, the nanoplatelets have on their edges functional groups such as ethers, carboxyls, or hydroxyls that can facilitate the GRA distribution into the matrix [42]. The results of this study suggest that the use of RES and 1% GRA is a promising approach for developing high-performance biodegradable blends with good structural integrity for use in automotive parts.…”
Section: Morphological Analysismentioning
confidence: 89%
“…The results showed that with the incorporation of RES and GRA, there was a decrease in the viscosity of the blends. Lima et al [42] evaluated the rheological behavior of polypropylene (PP)/GRA nanocomposites at 180 and detected a decrease in viscosity with the addition of GRA. The authors proposed that this reduction in viscosity could be attributed to a weak interaction between the polypropylene matrix and GRA.…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…[4,8] In the literature, there are various studies in which GNP was used as a filler to improve the final properties of polymers. [13,14] For instance, polypropylene, acrylonitrile butadiene styrene, and thermoplastic polyurethane have been studied by Caradonna et al [15] to enhance their properties. It was documented that GNP increased the thermal conductivity and stability of the polymers.…”
Section: Introductionmentioning
confidence: 99%